2011
DOI: 10.4047/jap.2011.3.4.229
|View full text |Cite
|
Sign up to set email alerts
|

A 5-year retrospective clinical study of the Dentium implants

Abstract: PURPOSEThe aim of this retrospective study was to evaluate cumulative survival rate (CSR) of Implantium implants followed for 5 years and association between risk factors and the CSR.MATERIALS AND METHODSA total of two hundred forty-nine Implantium Implants System (Dentium, Seoul, Korea) placed in ninety-five patients from 2004 to 2009 were investigated with several identified risk factors (sex, systemic disease, smoking, alchohol, reason of tooth loss, length, arch (maxilla or mandible), replace tooth type (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 21 publications
0
22
3
3
Order By: Relevance
“…This result is comparable with CSR results of previous studies of widely used titanium implants in Korean population with survival rate ranges from 95.4 -98.9% and follow up period from 5 to 9 years. 12,14,[23][24][25] Furthermore, 5 and 10-year retrospective clinical study of Implantium implants system (Dentium, Seoul, South Korea) and 7 years of Osstem implants (Osstem Implant Co., Ltd., Busan, Korea) reported a CSR of 97.27%, 97.9% and 95.37% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is comparable with CSR results of previous studies of widely used titanium implants in Korean population with survival rate ranges from 95.4 -98.9% and follow up period from 5 to 9 years. 12,14,[23][24][25] Furthermore, 5 and 10-year retrospective clinical study of Implantium implants system (Dentium, Seoul, South Korea) and 7 years of Osstem implants (Osstem Implant Co., Ltd., Busan, Korea) reported a CSR of 97.27%, 97.9% and 95.37% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 On the other hand, 7-year clinical study of Osstem implants revealed that implant survival rate was influenced with increased implant diameter, reduced prosthetic loading period and performance of bone graft.…”
Section: -14mentioning
confidence: 99%
See 1 more Smart Citation
“…The junction between the implant machined collar bevel and the microrough surface was used as the reference line. 39,40 The distance between the reference line and the most coronal implant-bone contact point was measured to the nearest 0.1 mm using Kodac R4 dental software. The value was positive when the implant-bone contact point was more coronal than the reference line and negative when the contact point was more apical to the reference line.…”
Section: Marginal Bone Level Changementioning
confidence: 99%
“…The overall dental implant failure rate is approximately 3% in all dental sites in upper and lower jaws (Lee, et al, 2011, Babbush, et al, 2012. The replacement of missing teeth by prosthetically restored implants in the molar region is particularly challenging as this region has greater occlusal forces than the anterior region of the mouth (Rossetti, et al, 2010) and therefore the amount of bone volume for fixture placement and restorative space is critical.…”
Section: Considerations For Optimal Placement Of Dental Implants In Tmentioning
confidence: 99%